Single centre experience of use of transarterial chemoembolization (TACE) with doxorubicin eluting beads (DEB) for the treatment of hepatocellular carcinoma (HCC). (13th March 2011) - Jamil, K; Fotiadis, N; Lowe, D; Kooner, P
Abstract : Introduction: There is evidence that TACE can prolong survival in patients with inoperable HCC, and DEB may provide even further benefit, with a favourable side effect profile. This is the first UK report of experience with this treatment modality. Methods: The authors performed a retrospective analysis of all patients receiving TACE with DEB for HCC at The Royal London Hospital between January 2009 and April 2010. Data collected included patient demographics, aetiology of liver disease and tumour characteristics. The Child-Pugh Score, Barcelona Clinic Liver Cancer (BCLC) stage, Cancer of the Liver Italian Programme (CLIP) score and Okuda stage were calculated. Complications following TACE were analysed and tumour response was assessed by 6-week post-treatment triphasic CT scanning (by mRECIST criteria). The authors also analysed overall survival to the end of follow-up. Results: During the study period 14 patients received 21 cycles of TACE with DEB. There were 11 males (79%), and mean age was 64 years (SD 8.3). The main causes of liver disease were hepatitis C (29%), hepatitis B (21%), alcohol (21%). The median number of liver lesions was 2 (range 1–7), and the mean size of the largest lesion was 5 cm (range 1.2–11.2 cm). All patients had Child Pugh Score A5 to B7, and 71% were BCLC stage B or C. The median CLIP score was 1 (range 0–2), and 79% were Okuda stage 1. The mean Doxorubicin dose was 119 mg (range 37.5–150 mg). The only complications were postembolisation syndrome of pain and fever in one patient and a haematoma in one patient, requiring conservative treatment only. These resolved with no long-term sequelae. There were no episodes of neutropenia at day 10. All patients had a radiological response observed on the 6-week triphasic CT scan. Tumour response (mRECIST partial and complete) was observed in 76% of cases and after a mean follow-up of 8 months (range 1–16) 13 patients (93%) were alive. Conclusion: TACE with DEB is a well tolerated and safe modality for treatment of inoperable HCC. This results demonstrate high rates of tumour response and a low complication rate. Further larger studies are warranted to evaluate this promising treatment.